"Workers' Rights are Human Rights": The Scope and Limits of a Precarious Wageworker's Strategy. Issue 1 (March 2016) - Caffentzis, George
Abstract : This essay examines the slogan, "Worker's Rights are Human Rights" which is the early twenty‐first century echo of the nineteenth's, "An injury to one is an injury to all." I analyze the implications of the strategy implicit in the twenty‐first century slogan for an anti‐globalization movement and its impact on the precarious wageworkers' struggle in the U.S. and internationally. I conclude that the nineteenth century shibboleth is more politically reliable.